2021
DOI: 10.1371/journal.pone.0252803
|View full text |Cite
|
Sign up to set email alerts
|

Enlightenment on oscillatory properties of 23 class B notifiable infectious diseases in the mainland of China from 2004 to 2020

Abstract: A variety of infectious diseases occur in mainland China every year. Cyclic oscillation is a widespread attribute of most viral human infections. Understanding the outbreak cycle of infectious diseases can be conducive for public health management and disease surveillance. In this study, we collected time-series data for 23 class B notifiable infectious diseases from 2004 to 2020 using public datasets from the National Health Commission of China. Oscillatory properties were explored using power spectrum analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 60 publications
4
19
0
Order By: Relevance
“…It is noticeable that we proposed a new method to make the clusters through the oscillatory frequency of each infectious disease. Clearly, we found that three clusters were dependent on their outbreak frequencies in a year, which is also consistent with the results in the class B diseases ( 17 ). This new classification method could help us better understand the epidemical features on their periodic properties.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…It is noticeable that we proposed a new method to make the clusters through the oscillatory frequency of each infectious disease. Clearly, we found that three clusters were dependent on their outbreak frequencies in a year, which is also consistent with the results in the class B diseases ( 17 ). This new classification method could help us better understand the epidemical features on their periodic properties.…”
Section: Discussionsupporting
confidence: 91%
“…Majority of the class C diseases showed a diseasing trend of the infectious number of people and change of the infection oscillation ( Table 1 ). Combining the results of the change of infection and its oscillation, we could draw conclusions that the infection number is always accompanied by its oscillatory strength for the class C diseases (class B diseases also obeyed with this law), which is consistent with the hybrid model ( 17 ). Besides, the oscillatory properties (frequency, preferred month) of a disease remains similar, hence the cluster would be stable using the current method.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations